The Effects of Transformational Leadership and Individual Motivation on Employee Performance: A Case Study of Maen Kain in the Creative Industry - Nafisah, Yeni Zulfa; Mansyur, Anwar (Manunggal Halim Jaya, 2026)
This study examines how transformational leadership and individual motivation influence employee performance in an MSME such as Maen Kain in Semarang, which relies heavily on employee craftsmanship and creativity, making leadership and motivation critical for organizational success. The motivation behind this research stems from the recognition that strong leaders who can inspire and motivate their teams are critical, especially in the creative industry, where innovation and high productivity are constantly in demand. To gather insights, a quantitative approach was taken, involving a survey of 106 full-time employees at Maen Kain. The data were analyzed using multiple linear regression with SPSS version 25. The key variables examined included transformational leadership and personal motivation as independent factors, with employee performance as the dependent outcome. The results show that transformational leadership does not have a significant direct effect on employee performance (β = –0.056, p > 0.05). In contrast, both intrinsic motivation (β = 0.240, p < 0.01) and extrinsic motivation (β = 0.274, p < 0.05) positively and significantly affect performance. The model explained 13.6% of the variance in performance (Adjusted R² = 0.136). These results suggest that at Maen Kain, internal motivation and employee engagement are more influential in driving performance than leadership style alone. Based on these insights, it is recommended that the company focus on strengthening work systems and encouraging ongoing self-development to boost motivation and sustain high performance.